The Role of Mobile Applications in Building Customer Loyalty: A Qualitative Study - İrem Elbir; Elif Eşiyok; Öykü Çalyan (Türkiye İletişim Araştırmaları Dergisi)
In an increasingly competitive environment, brands need to retain existing customers and attractpotential customers. Brands that employ various promotional activities to develop brand loyalty usedifferent strategies. Especially with the developments in technology and the increase in social mediause, mobile applications have become tools for these promotional activities. From this point of view,this study aims to examine the importance of mobile applications in creating customer loyalty. For thispurpose, the Starbucks brand, one of the leading coffee chains in the world, was selected. A qualitativeresearch method, semi-structured interviews, was conducted with 20 participants. While selecting theparticipants, customers who fit the definition of “loyal customer” in the literature were chosen. Thequestion form consisted of two parts. In the first part, information about the participants’ demographiccharacteristics was collected, and in the second part, questions related to the purpose of this researchwere asked. The findings of the research were examined under the following themes namely; loyaltydrivers of the customers, usage of mobile applications and customer loyalty, and impact of the mobileapplication on customer loyalty. Loyalty drivers of the customers were examined under three mainthemes as service-related choices, location of the stores, quality and taste. Besides, under the “Servicerelatedchoices” theme, internal environment and store atmosphere, and self-service sub-themes werediscussed. As a result, it was revealed that service related choices, quality-taste, and location of thestores are the drivers that effect customer loyalty. The mobile applications were not used frequently bythe consumers yet, and it was not found as a strong indicator of customer loyalty.